Pelatihan Pembuatan Podcast dan Content Creation SHHIDUO sebagai Wadah Pengembangan Produktivitas Kreativitas Bagi Siswa SMKN 2 Padang - Alamsyah, Devy Kurnia; Pangesti, Nesa Riska; Purnomo, Eko; Nablia, Mona Syifa; Mahdyyah, Difa Rosa (ABDI HUMANIORA: Jurnal Pengabdian Masyarakat Bidang Humaniora, 2025)
This study focuses on a training program titled "Podcast and Content Creation Training at SHHIDUO as a Platform for Enhancing Productivity and Creativity for Students of SMKN 2 Padang." With the increasing significance of digital content production, the program aims to equip students with technical and creative skills in podcasting and content creation. The SHHIDUO studio, a collaboration with JBICA Korea, serves as the venue but has been underutilized due to a lack of technical knowledge among students and teachers. This training, held on July 22-23, 2024, selected 15 top students and provided hands-on learning in areas such as audio recording, video editing, and content distribution. The program successfully enhanced students' digital skills and creative confidence, preparing them for future challenges in the digital media industry.